The Effect of Earnings Management and Internal Control on Tax Avoidance, with Political Connections as a Moderator - Rahayu; Lince Bulutoding; Suhartono (Journal of Applied Taxation and Policy, 2025)
This study aims to examine the effect of earnings management and internal control on tax avoidance, with political connections as a moderating variable. The research method used is purposive sampling with a total sample of 44 obtained from 11 selected companies. Data analysis was performed using multiple linear regression analysis and MRA testing. The results of this study indicate that earnings management does not have a positive effect on tax avoidance, while effective internal control has a negative effect on tax avoidance. The moderating variable of political connections does not moderate the effect of earnings management on tax avoidance but can weaken the effect of internal control on tax avoidance. Internal control not only prevents fraud in financial statements but also helps avoid tax avoidance practices. The implication of this study is that information related to the effectiveness of internal control can be one of the factors in determining a company's compliance, including in financial statement management, and companies that have political connections should maintain their relationships by avoiding practices that could damage the company's reputation and image.